The foundation of the CIA : Harry Truman, the Missouri Gang, and the origins of the Cold War - Schroeder, Richard E. (University of Missouri Press, 2017)
"This highly accessible book provides new material and a fresh perspective on American National Intelligence practice, focusing on the first fifty years of the twentieth century, when the United States took on the responsibilities of a global superpower during the first years of the Cold War. Late to the art of intelligence, the United States during World War II created a new model of combining intelligence collection and analytic functions into a single organization--the OSS. At the end of the war, President Harry Truman and a small group of advisors developed a new, centralized agency directly subordinate to and responsible to the President, despite entrenched institutional resistance. Instrumental to the creation of the CIA was a group known colloquially as the "Missouri Gang," which included not only President Truman but equally determined fellow Missourians Clark Clifford, Sidney Souers, and Roscoe Hillenkoetter."--Jacket